The effects of plyometric training on physical fitness in adolescent team sports: a systematic review and meta-analysis - Zhang, Fengming; Liu, Yang; Liu, Jiale; Yeremenko, Oleksandr; Shi, Lei (Frontiers in Physiology, 2026)
ObjectivesThis systematic review and meta-analysis examined the effects of plyometric training (PT) on the physical fitness of adolescent team-sport athletes.MethodsWe systematically searched the PubMed, Web of Science, Scopus, and Embase databases. The methodological quality of the studies was evaluated using the Cochrane Risk of Bias Tool (ROB-2). Meta-analyses were conducted using RevMan 5.4 and STATA 15.0.ResultsA total of 31 studies involving 1,033 athletes (906 males and 127 females) were ultimately included. PT improved jump performance, including countermovement jump (ES = 0.89), countermovement jump with arms (ES = 1.00), squat jump (ES = 0.48), and standing long jump (ES = 1.10). PT also improved linear sprint over ≤10-m (ES = −0.59), 20-m (ES = −0.42), and 30-m (ES = −0.97), and improved change-of-direction (ES = −0.73).ConclusionPlyometric training can significantly improve the jumping performance, linear sprint and change-of-direction in adolescent team-sport athletes. Athletes aged 16–18.99 years may show larger improvements, and interventions lasting ≥8 to <10 weeks may be associated with more consistent gains, particularly for Countermovement Jump, SJ, ≤10-m linear sprint, and 20-m linear sprint. In contrast, increasing the total number of jumps was not consistently associated with greater training effects.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251034889.